2017
DOI: 10.1016/j.virol.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Droplet digital PCR for rapid enumeration of viral genomes and particles from cells and animals infected with orthopoxviruses

Abstract: Droplet digital polymerase chain reaction (ddPCR) was adapted for quantifying the number of orthopoxviral genomes in purified virus samples, infected cell lysates and tissues of infected animals. In contrast to the more commonly used qPCR, the newer ddPCR provides absolute numbers of DNA copies in samples without need for standard curves and has the ability to detect rare mutants in a population. The genome/infectious unit ratio for several sucrose gradient-purified orthopoxviruses varied from 5 to 10, which c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 21 publications
0
23
0
Order By: Relevance
“…Total RNA was extracted at 8 h after infection with RNeasy RNA mini kit (Qiagen), quantitated with the nanodrop spectrophotometer and equal amounts of RNA were treated with DNase prior to reverse-transcription with a SuperScript IV First-Strand synthesis system using oligo-dT primers (ThermoFisher). Equal amounts of DNA or cDNA from each sample were then serially diluted and analyzed with gene-specific primers (E11L for viral genomic DNA) by ddPCR according to the protocol described previously using an automated droplet generator and the QX200 droplet reader (Bio-Rad) [ 46 ]. Primers used for mRNA quantification: I1L (5’ TGGAAAACTGGATGATACAGGCA 3’; 5’ TGTGTAGCGCTTCTTTTTAGTC 3’); A3L (5’ CTATAGACAAAATAGAAGCC 3’; 5’ CCATGATTAGAAAAGCAATTATG 3’).…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was extracted at 8 h after infection with RNeasy RNA mini kit (Qiagen), quantitated with the nanodrop spectrophotometer and equal amounts of RNA were treated with DNase prior to reverse-transcription with a SuperScript IV First-Strand synthesis system using oligo-dT primers (ThermoFisher). Equal amounts of DNA or cDNA from each sample were then serially diluted and analyzed with gene-specific primers (E11L for viral genomic DNA) by ddPCR according to the protocol described previously using an automated droplet generator and the QX200 droplet reader (Bio-Rad) [ 46 ]. Primers used for mRNA quantification: I1L (5’ TGGAAAACTGGATGATACAGGCA 3’; 5’ TGTGTAGCGCTTCTTTTTAGTC 3’); A3L (5’ CTATAGACAAAATAGAAGCC 3’; 5’ CCATGATTAGAAAAGCAATTATG 3’).…”
Section: Methodsmentioning
confidence: 99%
“…For genome particles quantification, real time polymerase chain reaction (qPCR) is usually the method of choice. Droplet digital polymerase chain reaction (ddPCR) has also been recently used for quantifying viral genome, without the need for a standard curve [154,155]. Depending on the final use of virus-based particles, and different from mAbs, infectivity can be a critical parameter.…”
Section: Analytics In Process Developmentmentioning
confidence: 99%
“…In this respect, only faeces obtained with non-invasive procedure is not allowed. Several studies have demonstrated the efficient dPCR platform searching different viruses [20][21][22][23][24][25]. Moreover, rapid, accurate and affordable molecular technology can be predictable with particular emphasis on emerging techniques (next generation sequencing, digital PCR, point of care testing and syndromic diagnosis) to simplify viral diagnosis in the next future [24,25].…”
Section: Resultsmentioning
confidence: 99%